COVID-19 in South Africa and the Containment of the Homeless, Drug, and Substance Users in Tshwane: A Gender Perspective - Newman Tekwa; Jennifer Makhubela (International Journal on Homelessness)
To curb the spread of the coronavirus disease of 2019 (COVID-19) in response to the national lockdown, the City of Tshwane, supported by law enforcement agencies, involuntarily rounded up all people experiencing homelessness. The group, comprising around 2,000 women, men, and children, was initially gathered at Caledonian stadium but subsequently ferried to emergency temporary male and female COVID-19 homeless containment shelters established across the City. While the rolling out of the COVID-19 emergency homeless shelters programme by the city was based on intentions of health protection, management challenges led to ongoing safety concerns. Adopting Bowers’s (2006) conflict and containment theory, this study investigates the relationship between conflict behaviours and containment measures within female and male COVID-19 temporary homeless shelters. Preliminary evidence from a mixed methods study suggests that male admission and drug and substance use increase the levels of conflict behaviours, and no association was found between an increase in security personnel and a reduction in conflict behaviours in COVID-19 shelters. A large proportion of conflict behaviours could be reduced by more efficient, effective, and improved service and by reducing the size of COVID-19 temporary homeless shelters, making the shelters less coercive and safer for residents and staff.